2023
DOI: 10.3390/jcm12041444
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes and Risk Factors in Orthognathic Surgery for Mandibular and Maxillary Hypo- and Hyperplasia: A 13-Year Analysis of a Multi-Institutional Database

Abstract: Background: Orthognathic surgery (OS) is a frequently performed procedure for the correction of dentofacial deformities and malocclusion. Research on OS is mostly limited to single-surgeon experience or single-institutional reports. We, therefore, retrospectively analyzed a multi-institutional database to investigate outcomes of OS and identify risk factors for peri- and postoperative complications. Methods: We reviewed the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The remaining sixteen studies reported risk assessments of orthodontic procedures or materials. These included safety assessment of dental radiography [ 23 ], bonding of brackets under general anaesthesia [ 24 ], orthodontic facebows [ 10 ], mini-implants [ 12 , 25 , 26 ], soft-tissue lasers in orthodontics [ 13 ], effect of orthodontic treatment on patients’ diet [ 14 ], eye safety of curing lights [ 27 ], safety of metal fixed appliance during magnetic resonance imaging (MRI) [ 28 ], pulp safety of various types of curing lights [ 29 ], wrong tooth extraction in orthodontics [ 30 32 ], orthodontic treatment by identifying orthodontic never events [ 33 ] and complications after orthognathic surgery [ 34 ]. These studies identified risks in orthodontic procedures or materials and proposed solutions to manage and minimise these risks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining sixteen studies reported risk assessments of orthodontic procedures or materials. These included safety assessment of dental radiography [ 23 ], bonding of brackets under general anaesthesia [ 24 ], orthodontic facebows [ 10 ], mini-implants [ 12 , 25 , 26 ], soft-tissue lasers in orthodontics [ 13 ], effect of orthodontic treatment on patients’ diet [ 14 ], eye safety of curing lights [ 27 ], safety of metal fixed appliance during magnetic resonance imaging (MRI) [ 28 ], pulp safety of various types of curing lights [ 29 ], wrong tooth extraction in orthodontics [ 30 32 ], orthodontic treatment by identifying orthodontic never events [ 33 ] and complications after orthognathic surgery [ 34 ]. These studies identified risks in orthodontic procedures or materials and proposed solutions to manage and minimise these risks.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the studies included provided information in the first category of the WHO’s research cycle on patient safety, which is “measuring harm” [ 4 , 7 9 , 19 , 22 , 34 ]. Sims et al conducted a postal survey on eye protection in the UK and found that ocular injuries were reported in 37.7% of all respondents involving orthodontists, assistants and patients [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential intraoperative adverse events in orthognathic surgery include abnormal hemorrhage due to infection or injury, fracture and split, osteonecrosis, etc. [25]. The mandible is identified as adverse-event-prone, probably due to its unique anatomical conditions, such as its masticatory muscle attachment, articulatory function, difficulties in visualizing the inferior alveolar neurovascular bundle and strict demands for osteotomy and fixation [26].…”
Section: Discussionmentioning
confidence: 99%